Implementasi Bahasa Inggris Teologi Sebagai English for Spesific Purpose (ESP) pada Perkuliahan Bahasa Ibrani di Prodi PAK STT Periago Jakarta - Marlan Hutauruk; Tri Agung Santoso; Hotliong Verawaty; Yehezkiel Situmorang; Astri Yulia Pogo (Program Studi Misiologi dan Komunikasi Kristen, 2023)
Learning Hebrew in practice requires a supporting language that has morphologically and grammatically close language forms. Theological English as English for Specific Purpose (ESP) the language of instruction in Hebrew lectures has benefits for students of the Christian Religious Education Study Program (PAK). Theological English (ESP) is the key for English being used as the language of instruction, especially in language courses because it can affect translation and provide practical benefits for students taking language courses. This research used a qualitative approach with data collection techniques through a survey at the Christian Religious Education Study Program of STT Periago Jakarta. English is important as the medium of instruction in Hebrew lectures, ESP as the medium of instruction in Hebrew lectures has benefits for students of the Christian Religious Education Study Program.